Power decoupling control for modular multilevel converter - Wang, Jinyu (2020)
The existing power decoupling control method of modular multilevel converter (MMC) was developed from that of conventional two-level voltage source converters. Therefore, it cannot fully realize power decoupling due to neglecting the coupling effects from submodule capacitor voltage, dc current, circulating current as well as control strategies of circulating current, which inevitably results in inaccurate regulation of active and reactive power, deteriorated system dynamic performance, possible overload operation and eventually threatens the safety and stability of MMC. This paper analyzes the intercoupling among all electrical quantities and corresponding control strategies in MMC. An accurate control model of active and reactive power/current with four coupling paths and influence factors in the rotating frame is also established. A full power decoupling control method has been proposed based on the developed model. The proposed control method can realize accurate and completely decoupled active and reactive power regulation, avoid overload operation, and significantly improve the dynamic performance of MMC. Moreover, it facilitates the parameters selection of MMC controller with no extra cost, which is of great significance for practical projects. The effectiveness and accuracy of the proposed analysis and control methods were verified by both simulation and experimental results.